Antioxidant Effect of Cocoa By-Product and Cherry Polyphenol Extracts: A Comparative Study - Francesca Felice; Angela Fabiano; Marinella De Leo; Anna Maria Piras; Denise Beconcini; Maria Michela Cesare; Alessandra Braca; Ylenia Zambito; Rossella Di Stefano (MDPI AG, 2020)
Background: Recent studies have highlighted the importance of cherry and cocoa extracts consumption to protect cells from oxidative stress, paying particular attention to cocoa by-products. This study aims to investigate the protective effect of cocoa husk extract (CHE) and cherry extracts (CE) against ROS-induced oxidative stress in Human Umbilical Vein Endothelial Cells (HUVECs). Methods: CE and CHE had antioxidant activity characterized by total polyphenols content (TPC). HUVECs were treated for 2 h and 24 h with increasing TPC concentrations of CE and CHE (5-10-25-50-100 µg Gallic Acid Equivalent (GAE)/mL) and then with H2O2 for 1 h. Cell viability and ROS production were evaluated. CE and CHE polyphenols permeability on excised rat intestine were also studied. Results: CE and CHE showed a similar antioxidant activity (2.5 ± 0.01 mmol Fe2+/100 g FW (fresh weight) and 2.19 ± 0.09 mmol Fe2+/100 g FW, respectively, p > 0.05) whereas CHE had a higher TPC (7105.0 ± 96.9 mg GAE/100 g FW) than CE (402.5 ± 8.4 mg GAE/100 g), p < 0.05. The in vitro viability assay showed that both extracts were non-cytotoxic. CHE resulted in protection against ROS at lower concentrations than CE. CHE showed a 2-fold higher apparent permeability compared to CE. Conclusions: CHE represents a high-value antioxidant source, which is interesting for the food and pharmaceutical industries.